Kombinasi Maltodekstrin dan Whey sebagai Bahan Penyalut padaKarakteristik MikroenkapsulOleoresinKayu Manis (Cinnamomum burmanii) - Tanalyna Hasna; Baskara Katri Anandito; Lia Umi Khasanah; Rohula Utami; Godras Jati Manuhara (agriTECH, 2018)
The aim of this study was to investigate the influence using combination of maltodextrin and whey (1:3, 2:2 and 3:1)  as wall material due to quality characteristic of cinnamon (Cinnamon burmanii) oleoresin microencapsulan, including yield, water content, solubility in water, microstructure appeareance, cinnamaldehyde content, and residue of solvent. First of all, the oleoresin was reached from extraction using ethanol 96 % for 4 hours. Then the oleoresin emultion was dried using spray drying method. The experimental design used in this research was Completely Randomized Design (CRD) with one factor (rasio of wall material). The result showed that combination of wall material had significant effect to yield (14,98 - 22,69%), water content (6,20 - 7,04%), residue of solvent (00,50 - 0,63%), cinnamaldehyde content (26,18 - 43,90%), and microstructure appeareance, but unsignificantly affected to solubility in water (92,85 - 95,24%).